Extracurricular Management of Madrasah Security Patrol Program (PKM) (Case Study at MAN 2 Padang) - Sinta, Sinta; Natsir, MHD (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
This research is motivated by an extracurricular program, the Madrasah Security Patrol Program (PKM), which is still relatively new and has good education at MAN 2 Padang City and has a myriad of achievements. This study aims to determine the management function of the extracurricular program, the Madrasah Security Patrol Program (PKM). This study uses a qualitative approach, with a case study research method. This research took place at MAN 2 Padang City, located at Jalan Gajah Mada No. 100 Padang, Padang Utara District, Gunung Pangilun Village, Padang City, West Sumatra Province. The researcher conducted a study on how to manage the extracurricular security patrol (PKM) at MAN 2 Padang City. The sources of this research were obtained from research subjects and research informants, namely the research subjects were the researchers themselves and the research informants were the supervisors, trainers, and members of the PKM extracurricular. Data collection techniques in this study were observation, interviews, and documentation. The data validity technique used triangulation techniques (methods, techniques, and sources). The results of the study show (1) the form of extracurricular planning for this PKM program is determining the organization's goals, determining what materials will be given to extracurricular members during one semester and the training schedule. (2) the form of organization in this PKM extracurricular is the formation of an organizational structure, determining the team leader or danton and forming small groups to practice different variations of movements. (3) providing motivation in this PKM extracurricular is providing words of advice, support, and encouragement to members each and after training. (4) supervision of PKM extracurricular activities is carried out directly. This supervision means that the instructor and trainer are directly involved in every activity that takes place. (5) there are several aspects that are assessed in this PKM extracurricular, namely: Attendance, Mastery of Material, Practice, Attitude, and Solidarity. The results of the assessment of these aspects will be included in the report card grades of extracurricular members.